Response of foxtail millet yield, soil chemical property and bacterial community to different green manure-foxtail millet rotation models in North China - Yu, Guohong; Han, Ya; Liu, Pengcheng; Hao, Hongbo; Li, Mingzhe (Frontiers in Microbiology, 2025)
China is a largely agricultural country, while the drought climate in northern of China is more and more severe, which influences on the agriculture production seriously. The over-exploitation of groundwater is a critical issue in the low plains of Hebei Province. To address this challenge, the government has implemented winter fallow and rain-fed crop planting policies. In alignment with these policies and ensure the sustainable utilization and protection of cultivated land, this study conducted long-term field experiments using three green manure with foxtail millet rotation models at Shenzhou District experimental base, Hengshui City, Hebei Province. Thefoxtail millet yield, soil bacterial community characteristicsc, and soil physicochemical properties were analyzed to identify an optimal green planting model for promoting sustainable agricultural development. The results revealed that three green manure-foxtail millet rotation models significantly increased millet yield compared to millet-rallow rotation. The foxtail millet–Triticum secale rotation model achieved the highest yield increase, with a 12.47% average improvement in thousand-seed weight in 2021 and 2022 compared to millet-fallow rotation. This rotation model also led to the largest increase in available phosphorus content, which rose by 46.16 and 37.56% in 2021 and 2022, respectively. Furthermore, the diversity and richness of the soil rhizosphere bacterial community were highest under this model. Beneficial bacterial genera, including those in the Phyla Bacteroidetes and Proteobacteria, were more abundant, while the relative abundance of Acidobacteria was lowest. Correlation analysis showed that soil organic matter, available phosphorus, and millet yield were positively correlated with multiple genera of Bacteroidetes and Proteobacteria but negatively correlated with Acidobacteria. In conclusion, the foxtail millet–Triticum secale rotation model effectively improved the soil environment and supported stable, high millet yields. These findings provide a theoretical basis for advancing crop rotation strategies and offer technical support for sustainable agricultural development.